Highly efficient and durable dye-sensitized solar cells based on a wet-laid PET membrane electrolyte. Issue 2 (8th December 2015) - Sun, Kyung Chul; Sahito, Iftikhar Ali; Noh, Jung Woo; Yeo, Sang Young; Im, Jung Nam; Yi, Sung Chul; Kim, Yeon Sang; Jeong, Sung Hoon
Abstract : Polyethylene terephthalate (PET), a commonly used textile fiber, was used in the form of a wet-laid non-woven fabric as a matrix for electrolytes in dye-sensitized solar cells (DSSCs). Abstract : Polyethylene terephthalate (PET), a commonly used textile fiber, was used in the form of a wet-laid non-woven fabric as a matrix for electrolytes in dye-sensitized solar cells (DSSCs). Also functioning as a separator between the photoanode and cathode of a DSSC, this non-woven membrane was prepared by a well-known wet-laid manufacturing process followed by calendaring to reduce the thickness and increase the uniformity of the structure. This membrane can better absorb the electrolyte turning into a quasi-solid, providing excellent interfacial contact between both electrodes of the DSSC and preventing a short circuit. An optimized membrane provides a better and more desirable structure for ionic conductivity, resulting in the improvement of the photovoltaic performance after calendaring. The quasi-solid-state DSSC assembled with an optimized membrane exhibited 10.248% power conversion efficiency (PCE) at 100 mW cm −2 . With the aim of increasing the absorbance, the membrane was also plasma-treated with argon and oxygen separately, which resulted in retention of the electrolyte, avoiding its evaporation, and a 15% longer lifetime of the DSSC compared to liquid electrolytes. The morphology of the membrane was studied by field emission scanning electron microscopy, and the photovoltaic properties and impedance spectroscopy of the cells were studied using polarization curves and electrochemical impedance spectroscopy, respectively. The results suggest that this novel membrane can be used in high-efficiency solar cells, increasing their lifetime without compromising the photovoltaic properties.